The comforts of home - Hill, Susan, 1942- (Hill, Susan, 1942- Simon Serrailler crime novels., 2018)
Investigating a cold case while recovering from a near-fatal injury, Simon Serrailler finds his personal and professional lives intertwining in unexpected ways when his constable brother-in-law suffers a setback at the same time an arsonist begins a deadly rampage.